Pengaruh Ekstrak Rebusan Daun Tithonia diversifolia (Hemsl.) A. Gray Terhadap Kadar Glukosa Darah - Rinawati Rinawati; E Suharyanto; Nastiti Wijayanti (Universitas Islam Negeri Ar-Raniry, 2019)
Tithonia diversifolia is a plant that has the potential to reduce blood glucose levels that is crucial in Diabetes Mellitus therapy. This study aims to determine the active compounds contained in the extract of T. diversifolia leaves decoction, the effect of decoction extract on the reduction of blood glucose, and the most effective decoction extract to reduce blood glucose levels as well. The study used a Completely Randomized Design (CRD) with the research treatment groups, namely: Kn = normal control (normal mice and not given leaves decoction extract), Ka = STZ control (DM mice, which are normal mice induced by 65mg/Kg of STZ), Kp = treatment control (normal mice given leaf decoction extract) , P1 = DM + mice were given young leaf decoction extract, P2 = DM + mice were given a mixture of young leaf and adult leaf decoction extract, P3 = DM + mice were given adult leaf decoction extract. The leaves used for decoction were 1-6 leaves from the shoots. The analysis of T. diversifolia leaves decoction compounds is using the visible spectrophotometers for tannins, phenols and flavonoids and GC-MS for terpenoid analysis. The result found that Tithonia diversifolia leaves decoction extracts contain tannins, flavonoids and phenols, while terpenoids are not detected. The leaves decoction extracts of T. diversifolia influenced the decreases in blood glucose levels of DM mice, especially the decoction extract of adult leaves which reduced blood glucose levels to 71.16%.